Authorship Pattern and Collaborative Research in the Field of Information Literacy (1981 to 2015) - ., Dr Dasanna; ., Devaraj (Journal of Advanced Research in Library and Information Science, 2021)
Scientometric techniques were applied to analyse the authorship pattern and collaborative trend in the field of information literacy for period 1981 to 2015. A total of 5682 papers were examined by year wise to ascertain authorship patterns, degree of collaboration and author productivity. 34.40% of papers were published with three authors and 18.76% of papers were with six authors. In the degree of collaboration of all years i.e. from 1981 to 2015 is 0.98 mean value is 0.5.